2003
DOI: 10.1016/s1631-0691(03)00157-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antioxidant and lignifying enzyme activities in sunflower roots (Helianthus annuus L.) stressed with copper excess

Abstract: Treatment with 50 µM CuSO 4 for five days caused significant decrease in dry-matter production and protein level of tenday-old sunflower seedling roots. An increase of lipoperoxidation product rate was also observed. The involvement of some enzyme activities in the sunflower root defence against Cu-induced oxidative stress was studied. Copper treatment induced several changes in antioxidant enzymes. SOD (superoxide dismutase, EC 1.15.1.1) activity was reduced but CAT (catalase, EC 1.11.1.6) and GPX (guaiacol p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 24 publications
8
63
0
Order By: Relevance
“…POD activity showed the largest increase (about 130.1%) at the copper concentration of 200 µmol; with increasing copper concentration it declined. These results are in agreement with the results of some other studies with several plant species that suggest increased peroxidase activity in response to elevated copper concentrations (Jouili andEzzedine 2003, Tanyolac et al 2007). POD activity correlates with copper concentration in plant shoots (Xiong and Wang 2005).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…POD activity showed the largest increase (about 130.1%) at the copper concentration of 200 µmol; with increasing copper concentration it declined. These results are in agreement with the results of some other studies with several plant species that suggest increased peroxidase activity in response to elevated copper concentrations (Jouili andEzzedine 2003, Tanyolac et al 2007). POD activity correlates with copper concentration in plant shoots (Xiong and Wang 2005).…”
Section: Resultssupporting
confidence: 93%
“…The results suggest that PAL activity in Jatropha curcas seedlings strongly depends on tissue type and copper concentration. PAL, a key component of plant phenylpropanoid metabolism, is also involved in plant defence against oxidative stress; it increases during biotic and abiotic stress caused by heavy metal, light (through its effect on phytochrome), and fungal infection (Jouili andEzzedine 2003, MacDonald andD'Cunha 2007). Regulation of PAL activity in plants is complex, as there are multiple PAL encoding genes, some of which are expressed only in specific tissues or only under certain environmental conditions (MacDonald and D'Cunha 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium accumulation in O. tenuiflorium leads to malondialdehyde production (a cytotoxic product of lipid peroxidation) through excessive generation of free radicals (Rai et al 2004). Early studies showed that copper can interact with a wide range of physiological and biochemical processes in plant species (Jouili & Ezzedine 2003;Draobzkiewicz et al 2004) by increasing the production of reactive oxygen species and free radicals. These substances can inturn damage cell membranes by binding to the sulphydryl groups of membrane proteins or by increasing rates of lipid peroxidation (Liu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, antioxidant capacity is dependant on the severity of the stress, on the species and/or on the stage of development (Dat et al, 2000). One of the most damaging oxidative effects is the peroxidation of membrane lipids, which results in the concomitant production of malondialdehyde (MDA), a secondary end product of polyunsaturated fatty acids (FA) oxidation (Hodges et al, 1999;Cho and Park, 2000;Jouili and El Ferjani, 2003). As a response to environmental stress, cells can modify their membrane lipid composition in order to maintain optimal physical properties (Thompson, 1992).…”
mentioning
confidence: 99%